The Effect of Flipped Classroom Model on ELE Students’ Reading Comprehension and Their Perception towards Flipping - Qonita Naylilhusna; Sintha Tresnadewi (Jurnal Pendidikan Humaniora, 2021)
Abstract: This quasi-experimental study aimed to find out the effect of the implementation of flipped classroom on ELE students’ reading comprehension and also observe their perception towards flipping. The findings of this study revealed that the difference in reading comprehension between students taught by using flipped classroom and those taught by using traditional classroom was significant. It was also found that the students in the experimental group have positive perception toward the use of flipped classroom teaching model. This implied that this technique could be applied effectively to teach reading comprehension for ELE students.Keywords: flipped classroom, reading comprehension, perceptionAbstrak: Penelitian quasi-experimental ini bertujuan untuk melihat pengaruh penerapan flipped classroom terhadap pemahaman membaca mahasiswa pendidikan bahasa Inggris (PBI) dan juga untuk mengamati persepsi mereka terhadap teknik tersebut. Hasil penelitian ini mengungkapkan bahwa ada perbedaan yang signifikan  pada pemahaman membaca mahasiswa antara mahasiswa yang diajar dengan menggunakan flipped classroom dan mahasiswa yang diajar secara tradisional. Ditemukan juga bahwa mahasiswa pada kelompok eksprimen memiliki persepsi positif terhadap penggunaan model pembelajaran flipped classroom. Ini menyiratkan bahwa   teknik ini dapat diterapkan secara efektif untuk mengajarkan pemahaman membaca mahasiswa PBI.Kata kunci: flipped classroom, pemahaman membaca, persepsi